Moisture buffer, fire resistance and insulation potential of novel bio-clay plaster. (30th May 2020) - Jiang, Yunhong; Phelipot-Mardele, Annabelle; Collet, Florence; Lanos, Christophe; Lemke, Manfred; Ansell, Martin; Hussain, Atif; Lawrence, Michael
Highlights: The bio-clay plaster can reduce material costs and environmental impact. The bio-clay plaster has good insulating and hygric properties. The bio-clay plaster exhibited improved fire resistance. The bio-clay plaster protective layer can maintain high water vapour permeation and improve indoor comfort for the building. Abstract: The novel bio-clay plaster was formulated by adding hemp powder to clay plaster to improve the performance of buildings by moisture buffering the indoor climate, providing a fire insulation layer to encapsulate inflammable bio-based substrates and enhancing air tightness within the system by closing joints. The results showed the plaster formulation influences drying shrinkage, thermal conductivity, density and the moisture buffer value of the plaster. The thermal conductivity of the novel bio-clay plaster decreased with a decreasing proportion of Earthen Clay. The proportion of hemp powder had little effect on the thermal conductivity of the plaster, whereas the amount of hemp powder had a slightly effect on the moisture buffering property. The novel bio-clay plaster exhibited improved fire resistance. The detailed hygrothermal characterization using the measurement of moisture buffer value and thermal conductivity analysis indicated that the novel bio-clay plaster showed a good moisture buffering capability, even for small thicknesses, and low thermal conductivity, with the potential to develop industrially viable products.